2021
DOI: 10.3390/ijerph182211989
|View full text |Cite
|
Sign up to set email alerts
|

Can the Development of Religious and Cultural Tourism Build a Sustainable and Friendly Life and Leisure Environment for the Elderly and Promote Physical and Mental Health?

Abstract: From the perspective of satisfaction, physical and mental health, and re-travel, this study explored whether the development of religious and cultural tourism could construct a sustainable and friendly life and leisure environment for the elderly to promote physical and mental health. This research adopted a mixed method, collected 700 questionnaires, used SPSS 22.0 statistical software, and analyzed basic statistics, t-test, and PPMCC test. Then, the researchers conducted semi-structured interviews, collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
25
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 67 publications
8
25
7
2
Order By: Relevance
“…Through the perception of leisure satisfaction, we can find the changes in personal leisure satisfaction after medical staff engage in swimming (36). Finally, the physical and mental health perception can be used to understand the improvement of personal physical and mental health after medical staff engages in swimming (37)(38)(39). These answers can be corroborated by participants' feelings (34,40,41).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Through the perception of leisure satisfaction, we can find the changes in personal leisure satisfaction after medical staff engage in swimming (36). Finally, the physical and mental health perception can be used to understand the improvement of personal physical and mental health after medical staff engages in swimming (37)(38)(39). These answers can be corroborated by participants' feelings (34,40,41).…”
Section: Introductionmentioning
confidence: 91%
“…Although the impact of participating in tourism activities during the epidemic has also been discussed (33,36,43,44), methods to improve people's health benefits have also been proposed, such as Qigong (6), intermittent fitness exercises (7), mountain climbing (4), and jogging (8). More recently, related impacts of leisure, travel, living and working environment, physical and mental health have also been discussed (36)(37)(38), as well as environmental risks, satisfaction, and physical and mental health issues (40,41,45). However, the researchers found that swimming was not discussed as a topic, and the environmental risks, physical anxiety, leisure satisfaction, and physical and mental health perceptions of healthcare workers engaged in swimming in SARS-CoV-2 settings.…”
Section: Introductionmentioning
confidence: 99%
“…With the evolution of time, these religious sites and historical relics have become tourist sites with historical, cultural, and tourism values [ 20 ]. Thus, religion is a kind of representation of human civilization with local cultural and historical significance and rich in leisure and tourism resources [ 21 ]. It can be a motivation for people to engage in leisure or tourism activities, sightseeing, site visit, worship, study, and meditation [ 22 ], and has the functions of boosting the confidence of the masses, reducing their anxiety [ 23 ], and achieving healthy social development [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies have shown that there are differences between the expected effects of decision-making and the actual effects [ 20 , 21 , 37 , 38 , 39 ]. Different environments and human or non-human factors may cause this difference [ 21 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation